2012
DOI: 10.1007/s00264-012-1702-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical performance of different cable and wire cerclage configurations

Abstract: Purpose Cerclage technology is regaining interest due to the increasing number of periprosthetic fractures. Different wiring techniques have been formerly proposed and have hibernated over years. Hereby, they are compared to current cerclage technology. Methods Seven groups (n06) of different cable cerclage (Ø1.7 mm, crimp closure) configurations (one single cerclage looped once around the shells, one single cerclage looped twice, two cerclages each looped once) and solid wire cerclages (Ø1.5 mm, twist closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 11 publications
1
57
1
2
Order By: Relevance
“…A number of options have been proposed ranging from combinations of long stem femoral components, extramedullary fixation with cerclage cables, plates, and strut grafts [6][7][8]15,17]. Several studies have previously demonstrated differences in fixation technique and biomechanical advantages of various cerclage constructs in fixation of periprosthetic femur fractures [8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Although metallic cerclage cables have been previously shown to provide more strength than twisted monofilament wire, cable use is associated with other complications and limitations in minimally invasive applications [18][19][20][21][22]32].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A number of options have been proposed ranging from combinations of long stem femoral components, extramedullary fixation with cerclage cables, plates, and strut grafts [6][7][8]15,17]. Several studies have previously demonstrated differences in fixation technique and biomechanical advantages of various cerclage constructs in fixation of periprosthetic femur fractures [8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Although metallic cerclage cables have been previously shown to provide more strength than twisted monofilament wire, cable use is associated with other complications and limitations in minimally invasive applications [18][19][20][21][22]32].…”
mentioning
confidence: 98%
“…Several studies have previously demonstrated differences in fixation technique and biomechanical advantages of various cerclage constructs in fixation of periprosthetic femur fractures [8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Although metallic cerclage cables have been previously shown to provide more strength than twisted monofilament wire, cable use is associated with other complications and limitations in minimally invasive applications [18][19][20][21][22]32]. As a result, there has been a renewed interest in wire cerclage systems and newer materials such as synthetic cables have emerged as potential alternatives to traditional metallic cables [23][24][25][33][34][35].…”
mentioning
confidence: 99%
“…Cable wiring is a simple technique that can be done with a minimally invasive approach [25] with proven clinical efficiency [25,26]. Doubling the cable wire around the diaphysis seems to give the best mechanical stability [13]. Another option, which is technically more challenging in a minimally invasive approach, is the use of the LAP.…”
Section: Discussionmentioning
confidence: 99%
“…If proximal fixation is not possible due a bulky stem, stabilisation must be assured by one or more cable wires to avoid breakout forces on the plate. Mechanically, stability is better when two cable wires are used or one cable is wrapped twice around the diaphysis [13]. Some authors suggest additional plates, like LAP with excellent mechanical stability [8,14] and satisfying clinical results [15].…”
Section: Osteosynthesis Guidelinesmentioning
confidence: 98%
“…Different techniques using monocortical screws, cerclage wires, additional plates (e.g. locking attachment plate; Synthes, Umkirch, Germany) or combinations have been described in order to achieve a stable fixation next to the prosthetic stem [7,14,15]. Biomechanical studies investigated the stability of the different fixation options and concluded that stand-alone cerclage wires are insufficient [7,16,17].…”
Section: Introductionmentioning
confidence: 98%